2020
DOI: 10.3390/ijms21186546
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation-Associated Alterations of the Brain as Potential Neural Biomarkers in Anxiety Disorders

Abstract: Stress-induced changes in the immune system, which lead to neuroinflammation and consequent brain alterations, have been suggested as possible neurobiological substrates of anxiety disorders, with previous literature predominantly focusing on panic disorder, agoraphobia, and generalized anxiety disorder, among the anxiety disorders. Anxiety disorders have frequently been associated with chronic stress, with chronically stressful situations being reported to precipitate the onset of anxiety disorders. Also, chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 188 publications
(223 reference statements)
2
37
0
Order By: Relevance
“… 42 The activated microglial cells will led to the release of proinflammatory cytokines such as IL-1β, TNF-α, and IL-6, which exert direct neurotoxic effects on the brain. 43 Proinflammatory cytokines stimulate the HPA axis to release cortisol that further exacerbates the systemic stress response, and prolonged exposure to cortisol can impair inflammatory regulation by reducing the sensitivity of the peripheral immune systems to anti-inflammatory feedback, thus constituting a vicious cycle. 42 This has led to suggestions that increased levels of proinflammatory cytokines are a biomarker for depression.…”
Section: How Peripheral and Central Inflammation Processes Affect The Brainmentioning
confidence: 99%
“… 42 The activated microglial cells will led to the release of proinflammatory cytokines such as IL-1β, TNF-α, and IL-6, which exert direct neurotoxic effects on the brain. 43 Proinflammatory cytokines stimulate the HPA axis to release cortisol that further exacerbates the systemic stress response, and prolonged exposure to cortisol can impair inflammatory regulation by reducing the sensitivity of the peripheral immune systems to anti-inflammatory feedback, thus constituting a vicious cycle. 42 This has led to suggestions that increased levels of proinflammatory cytokines are a biomarker for depression.…”
Section: How Peripheral and Central Inflammation Processes Affect The Brainmentioning
confidence: 99%
“…Anxiety can cause fatigue, pain, and sleep disorders, and even reduce motivation and coping abilities, thus having a negative effect on patient compliance with treatment plans [26]. Moreover, anxiety is associated with chronic stress, and chronically stressful situations pre-cipitate the occurrence of anxiety disorders [27]. Fatigue is a common symptom experienced by cancer patients undergoing chemotherapy [28], and some of these patients experience cognitive impairment such as memory problems [29].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on 675 persons with epilepsy, and 2025 matched control subjects, reported that epileptic persons, age 50 years or above, have a greater risk of developing dementia than people without epilepsy [ 17 ]. Neuroinflammation is also a pathogenesis factor in other brain disorders, including Parkinson’s disease, amyotrophic lateral sclerosis and anxiety disorders [ 18 , 19 ].…”
Section: Alzheimer’s Diseasementioning
confidence: 99%